Новый вид рода Amphilagus (Lagomorpha, Palaeolagidae) из среднего сармата Украины - Топачевский, И.В. (Вестник зоологии, 1987)
Ampluilagus sarmaticus sp. n. is described from middle Sarmat deposits of the right bank of the Ukraine. The species is distinct with the presence of the basal collar, conlouring Р2 forewards, and undcep Titanomus-like incoming fold in Р3 Р4 — М1 have only one complex root.